Kritik Ignaz Goldziher dan Pembelaan Musthofa al Azami terhadap Hadis dalam Kitab Shahih al-Bukhari - Siska Helma Hera (Jurnal Living Hadis, 2020)
Criticism of the hadith will always appear, even though the scholars have agreed that the hadith is valid. This can be seen from the Sahih Bukhari book, which has been agreed by the ulama’ as a valid hadith book, but still received criticism from an orientalist named Ignaz Goldziher. Ignaz revealed that not all hadith listed in Sahih Bukhari are authentic, some of them are dhaif and maudhu’. In addition, Ignaz criticized the method used by Imam al Bukhari in researching hadith. According to him, Imam al Bukhari only focused on sanad and forgot the matan. Ignaz's criticism led to the conclusion that the traditions contained in Sahih Bukhari were not authentic from the Prophet Muhammad. According to him, these traditions were the result of fabrication by the generations after the Prophet. This conclusion is also corroborated by the reason for the codification of the hadith that occurred long after the Prophet generation. Responding to Ignaz's criticism, Musthofa al Azami (Muslim scholar) revealed that all of Ignaz's criticisms were baseless and could not be validly established as truth.